Perlindungan Hak Cipta: Perspektif Hukum Terhadap Tindak Pidana Pembajakan (Lembaga Pengabdian Masyarakat Universitas Ichsan Gorontalo, 2025)
This research discusses the legal protection of copyright with a focus on the criminal act of digital content piracy in Indonesia. Using normative legal research methods, this study highlights criminal penalties, the concept of restitution, and the impact of digital technology on copyright infringement. Primarily, the research explores the legal response to movie, music, and software piracy, detailing the criminal penalties provided for in Law Number 28 of 2014 on Copyright. In the context of digital technology, the research examines the role of technology in enhancing and challenging law enforcement against copyright infringement. The research conclusion emphasizes the importance of adaptive regulation, educational campaigns, and cross-sector collaboration, supported by the utilization of technology to enhance the effectiveness of law enforcement.